Pragmatics Analysis Of Persuasive Expressions Of Advertisement Of The Jakarta Post February 10-16 2014 - Byantara, Pria Adi, Dra. Siti Zuhriah Ariatmi, M.Hum, Dra. Malikatul Laila, M. Hum (2014)
This study aims to describe the linguistic forms of persuasive expression and to explain the intended meanings of persuasive expression found in the advertisement of The Jakarta Post February 10-16 2014. This is a descriptive qualitative research. The researcher collected the data by using methods of observation and documentation. The data includes field note of reading,underlying, classifying, rewriting and coding. The techniques used in analyzing data are as follows:reading the data of persuasive expression, underlying the data, analyzing the data from the result of observation and classifying, and concluding the result and giving suggestion. The results of the study shows that there are 22 of persuasive expression. There are six kinds of persuasive expression from twenty two data found in advertisement of The Jakarta Post. They are imperative sentence (31,9%), declarative sentence (27,3%), independent clause (4,5%), noun phrase (27,3%), compound noun phrase (4,5%)and verb phrase (4,5%). The types of persuasive expression found in advertisement of The Jakarta Post dominated by imperative sentence. The types illocutionary meanings are(4,5%) of convincing, (4,5%) of informing, (4,5%0 of emphasizing, (59,5%) of describing, (4,5%) of persuading, (9%) of explaining, (4,5%) of imaging, (4,5%) of inviting and (4,5%) of suggesting. The illocutionary acts mostly appear in the advertisement is describing.The total is 22 (100%) of persuasive expressions.